PENCIPTAAN BUKU ILUSTRASI REGALIA KERATON NGAYOGYAKARTA HADININGRAT SEBAGAI UPAYA PENGENALAN FILOSOFI KEPEMIMPINAN JAWA KEPADA REMAJA - Permadi, Dimas Nugroho Azis; Fianto, Achmad Yanu Alif; Fahminnansih, Fenty (Jurnal Art Nouveau, 2015)
Abstract: The creation of an illustrated book based media form as a depiction of local wisdom contained in Regalia Keraton Ngayogyakarta Hadiningrat is a study that aims to introduce the philosophy of Java to youth leadership. By using descriptive qualitative analysis method The processed data from interviews, observation and literature, drawn a conclusion that is used as the concept of creation. The concept of creation found is